HUBUNGAN SOCIAL COMPARISON DAN SENSE OF BELONGING: MODERASI EMOTIONAL INTELLIGENCE PADA REMAJA PENGGUNA INSTAGRAM - Cherry Delfina Setiawan; Riana Sahrani (Fakultas Psikologi Universitas Tarumanagara, 2026)
Adolescence is a crucial period for the development of social relationships. The presence of social media platforms such as Instagram has made social interaction more flexible. Adolescents use Instagram to express themselves, seek entertainment, and maintain social connections. At this stage, sense of belonging becomes important because it reflects the extent to which individuals feel connected to and accepted within their social groups. To understand their position in the social environment, adolescents often engage in social comparison, which involves evaluating themselves by comparing their opinions or abilities with others. Emotional intelligence helps individuals interpret these comparisons, which may influence their sense of belonging. This study aims to examine the relationship between social comparison and sense of belonging, with emotional intelligence as a moderating variable among adolescent Instagram users. This research employed a quantitative approach with purposive sampling. The instruments used were the Iowa-Netherlands Comparison Orientation Measure (INCOM), the Sense of Belonging on Social Media Scale (SOBOSM), and the Brief Emotional Intelligence Scale (BEIS-10), all adapted into Indonesian. Participants consisted of 386 late adolescents aged 18–21 years who had actively used Instagram for more than three months. Pearson correlation analysis showed a negative and significant relationship between social comparison and sense of belonging (r = -0.213, p < 0.01). Moderated Regression Analysis (MRA) showed that emotional intelligence weakened the negative effect of social comparison on sense of belonging.